The Effects of Promotion, Trust, Perceived Usefulness, And Perceived Ease of Use on Intention to Use - Hersindu, Aloysius Ardeyno Wilsananda; Puspaningrum, Astrid (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Purpose –  This study aims to examine the effects of promotion, trust, perceived usefulness, and perceived ease of use on the intention to use ShopeePay among non-users in Malang City.   Design/methodology/approach –   This study employs a quantitative explanatory research design to analyze the causal relationships between promotion, trust, perceived usefulness, perceived ease of use, and intention to use. Data were collected from 200 respondents aged at least 17 years who reside in Malang City and had not previously used ShopeePay. A non-probability sampling method with purposive sampling technique was applied. The data were analyzed using multiple linear regression with IBM SPSS Statistics 27.0, supported by instrument testing, classical assumption tests, and hypothesis testing.   Findings – The results indicate that promotion, trust, and perceived ease of use have positive and significant effects on intention to use ShopeePay, while perceived usefulness does not have a significant effect. These findings suggest that external incentives, trust factors, and ease of system interaction play a more dominant role than perceived usefulness in shaping adoption intention among potential users.   Originality/value – This study contributes to the technology acceptance literature by examining non-users’ intention to adopt digital payment services in an emerging market context. It highlights the relative importance of promotional influence, trust, and usability over perceived usefulness in driving adoption intention for ShopeePay.